Parametermeasurement of aircraft-radiated noise from a single acoustic sensor node in three-dimensional space - Yu, Shuwen; Xiao, Lei; Sun, Weitao (Frontiers in Marine Science, 2022)
A line spectrum presents the form of a narrow-band time-varying signal due to Doppler effect when the single hydrophone node observes flight-radiated noise. The modulation law of the time-varying signal contains a large number of feature information of moving targets, which can be used for detection and classification. This paper studies the possibility of using instantaneous frequency measurements from the hydrophone node to improve the precision of the flight parameter estimates when the source spectrum contains a harmonic line of constant frequency. First of all, we build up and analyze the underwater sound field excited by the aircraft using the ray theory model; then the Doppler shift in the two isospeed media, which is caused by the aircraft, is established; finally, a robust time–frequency transform describes the time–frequency distribution of the received signal, and a geometric approach solves the flying parameters.